2014
DOI: 10.1353/lm.2014.0010
|View full text |Cite
|
Sign up to set email alerts
|

The Medical Case Narrative: Distant Reading of an Epistemic Genre

Abstract: In this article, I argue that we should consider the medical case narrative as an “epistemic genre.” I suggest that historians of knowledge (including medical knowledge) should draw a distinction between “epistemic” and “literary” genres, and that the medical case narrative belongs to the first group, that is, those kinds of texts that develop in tandem with scientific practices. I also argue that the history of the medical case narrative should be studied in a long-term perspective. In general, the focal poin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(33 citation statements)
references
References 33 publications
0
32
0
1
Order By: Relevance
“…For instance, Gianna Pomata’s research has been pathbreaking for a longue durée history of the medical case. Her reflections on the medical case as an ‘epistemic genre’ refine Forrester’s notion of the case as a ‘style of thinking’, in that the concept puts emphasis on the textual nature of the case and the emic and social character of the category of genre (Pomata, 2010, 2013, 2014). Essentially, Pomata suggests that epistemic genres differ from literary genres in that they ‘develop in tandem with scientific practices’, and are ‘directly related with the making and the transmission of knowledge’ (Pomata, 2013: 133).…”
Section: Travels Of Cases In the History Of Medicine And Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Gianna Pomata’s research has been pathbreaking for a longue durée history of the medical case. Her reflections on the medical case as an ‘epistemic genre’ refine Forrester’s notion of the case as a ‘style of thinking’, in that the concept puts emphasis on the textual nature of the case and the emic and social character of the category of genre (Pomata, 2010, 2013, 2014). Essentially, Pomata suggests that epistemic genres differ from literary genres in that they ‘develop in tandem with scientific practices’, and are ‘directly related with the making and the transmission of knowledge’ (Pomata, 2013: 133).…”
Section: Travels Of Cases In the History Of Medicine And Literaturementioning
confidence: 99%
“…: 482). Although medical cases are usefully understood as an epistemic genre because they are ‘vehicles of a cognitive project’, a medical case – like other genres – can have both a history as an epistemic genre and a history as a literary genre, depending on the contexts in which it is used and the purposes for which it is employed (Pomata, 2014: 3). If we take this for granted, Cohen’s broad characterisation of traveling genres in literature can also apply to the medical case narrative, as my case study of an individual medical case shows.…”
Section: Travels Of Cases In the History Of Medicine And Literaturementioning
confidence: 99%
“…The discussion in this paper seems to re-orient our thinking: away from generalisation from case studies, towards generating knowledge through cases, insofar as we have described dialogical single case studies as concerned with dynamic and ethical interdependencies that can be accounted for in the identification of chronotopes, and suggested that chronotope may be characterised as a dialogical epistemic genre. Knowledge genres or epistemic genres have been discussed in relation to social epistemology in general (Berkenkotter & Tuckin, 1993), to narratives in medicine (Pomata, 2014) and to single case studies (Morgan, 2012). Although Morgan does not refer to Bakhtin, by 'epistemic genre' she means a thinking style or a way of thinking.…”
Section: Chronotopes and Generalisation In Dialogical Case Studies: Tmentioning
confidence: 99%
“…For the concept of "qualified experience" in Galen, see VAN DER EIJK, 1997. 72 On the case and the commentary as "epistemic genres", see POMATA, 2014. challenged itself in this process. In the end, the text constructs a possible coexistence of knowledge derived from empirical examination and revelationwithout smoothing away their generic or ontological difference.…”
Section: Know Ing Bodies Of Know Ledgementioning
confidence: 99%